Challenges and potential solutions to social inclusion in an aggregator model to promote weather index insurance in Bangladesh - CGIAR Research Program on Water, Land and Ecosystems; International Water Management Institute (International Water Management Institute, 2020)
Bangladesh is located in the low-lying river delta formed by the Ganges, Brahmaputra and Meghna rivers, and is considered as the country most vulnerable to climate change in the world (World Bank 2012). Furthermore, the country’s geography, population density and extreme poverty make Bangladeshi people highly vulnerable to other natural hazards, which often turn into disasters. Among the various risks and disasters, flooding is the most common and frequent, and is considered to be one of the principal threats to development. Approximately 70% of Bangladesh’s population is at risk of flooding.